Transformasi Peran dan Kapasitas Perempuan Rumah Tangga dalam Pengelolaan Sampah Rumah Tangga di Kota Makassar - Ratnawati Gatta; Nani Anggraini; Jumadil; Marini Mallagennie; Dahlia D. Moelier; Hadijah; Andi Fauziah Yahya; Muh Asy’ari (Jurnal Penyuluhan, 2022)
Makassar is one of the cities with the largest population in Indonesia so that the volume of waste that goes to the landfill is quite large. The most common type of waste is organic waste, which generally comes from households. Therefore, the target of this activity is women in the household as the controller of domestic affairs. The purpose of this activity is to know the transformation of the role of women in reducing and handling their household waste. The method used is qualitative descriptive method conducted through interview, observation and document study. The activities were carried out in the form of: (1) Household waste management socialization, (2) Training on reducing and handling household waste, (3) Practice of making composter and Biopore Infiltration Holes (LBR), (4) Assistance in the use of compost and processing of anorganic waste into useful items in the household. The results of the activity show that transformation of knowledge and the role of household women regarding household waste management, as well as increasing creativity and innovation of household women in processing waste so that it has economic value. What needs to be done next is to support the spirit of households in waste management through the establishment of community-based waste management partnership institutions and networks.